Finding patterns of extreme climate events in the South China Sea : a study of cold surges in Taiwan - Fu, Ziyue (2017)
Cold surge is one of the most extreme climate events during the Winter Monsoon yet its impact on the South China Sea (SCS) has not been studied in extensive detail. Taiwan, located at the northern end of the SCS, has traditionally been severely affected by the occurrence of cold surge events during winter but limited studies have taken a close look at this region. This Final Year Project (FYP) study analysed time series data from the past ten winters and found that the cold surge frequency exhibited aperiodic fluctuation. Weak correlations were found between temperature and pressure variations. Given the complex local topographic features in Taiwan, ranging from the Central Mountain Range (CMR) to the narrow Taiwan Strait, it was hypothesized that the surface conditions during a cold surge are different within the Taiwan region and the regions in its vicinity. Therefore, this study further used the European Centre for Medium-Range Weather Forecasts (ECMWF) Reanalysis data to construct composite time series charts and synoptic maps to analyse these differences caused by the interactions between the cold surge and local terrains. The composite time series confirmed the hypothesis as visible and consistent characteristics were observed in the four selected regions in Taiwan. The synoptic maps further demonstrated the reasons for these characteristics via the progression of two representative cold surge cases analysed.